1992
DOI: 10.1136/bjo.76.4.250
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral macular coloboma and pigmented paravenous retinochoroidal atrophy.

Abstract: A patient had bilateral macular coloboma with aggregations of pigment clumps located perivascularly, predominantly paravenously, and in other parts of the retina. The Toxoplasma IgG antibody was negative. The diagnosis of bilateral macular coloboma with pigmented paravenous retinochoroidal atrophy was made and seemed to be a developmental abnormality in origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 13 publications
0
28
0
1
Order By: Relevance
“…Bilateral macular coloboma was reported by Chen et al in a 23-year-old woman. 12 Our case had bilateral cystoid macular edema which was one of the manifestations of active inflammation, and as far as we are aware this has not been previously reported. Fluorescein angiography gave a better definition of the lesions as well as cystoid macular edema.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Bilateral macular coloboma was reported by Chen et al in a 23-year-old woman. 12 Our case had bilateral cystoid macular edema which was one of the manifestations of active inflammation, and as far as we are aware this has not been previously reported. Fluorescein angiography gave a better definition of the lesions as well as cystoid macular edema.…”
Section: Discussionmentioning
confidence: 84%
“…1 Chen et al reported a case with bilateral macular coloboma, PPRA and negative laboratory examinations and he speculated that it was a developmental abnormality in nature. 12 Some reports suggest an inflammatory cause. Syphilitic aetiology has been suggested by Chi Hsin-Hsiang.…”
Section: Discussionmentioning
confidence: 99%
“…This inherited association may represent an AD clinical entity, hitherto reported only in nonfamilial sporadic cases in which the progressive tapeto-retinal dystrophy was not always a well-defined entity and, hence, heterogeneously named. 4,[9][10][11] On the other hand, a chance of co-occurrence cannot be ruled out. In fact, the variable RP expressivity, milder in the female than those observed in the males, without any significant clinical difference in the macular colobomatous lesions, could be similarly claimed to justify the different clinical pictures found in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…14,17,18,20,21 Several cases of bilateral macular coloboma associated with different manifestations of peripheral chorioretinal inherited dystrophy have been previously reported. [4][5][6][7][8][9][10][11] Also, keratoconus has been described in patients with these ophthalmoscopic findings, but they were always nonfamilial cases. 4,5 The male members of this Caucasian family were affected by different typical RP phenotypes, 20,21 characterised by the presence of mid-peripheral bone spicules involving, respectively, the entire retina (classic RP; Case 1 and also the deceased father of the siblings) and only a retinal sector (sector RP; Case 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation